Effect of different imidazolium-based ionic liquids on gel polymer electrolytes for dye-sensitized solar cells - Syairah, Aimi; Khanmirzaei, M.H.; Saidi, Norshahirah M.; Farhana, N.K.; Ramesh, Subramaniam; Ramesh, Kasi; Ramesh, Singh (Springer Verlag (Germany), 2019)
Host polymer electrolytes are prepared using poly(ethylene oxide) (PEO) as a polymer, ethylene carbonate (EC) and propylene carbonate (PC) as solvents, sodium iodide (NaI) as salt, and iodine (I2) and with either one of the ionic liquids (ILs) which are 1-methyl-3-propylimidazolium iodide (MPII), 1-butyl-3-methylimidozium (BMII), and 1-hexyl-3-methylimidozium iodide (HMII) in each gel polymer electrolyte. The ionic conductivity of the gel polymer electrolytes (GPEs) was measured by electrochemical impedance spectrometer (EIS). The ionic conductivity of GPEs increased with the presence of ionic liquids (ILs). At room temperature, the dielectric behaviors of the GPEs were studied. The highest ionic conductivity of 9.41 mS cm−1 is achieved after addition of MPII ionic liquid. Meanwhile, Fourier-transform infrared and X-ray diffraction studies confirm complexation between PEO polymer, NaI salt, and ionic liquids (MPII, BMII, and HMII). Dye-sensitized solar cells (DSSCs) were fabricated using polymer electrolytes and studied under Sun simulator. The DSSC using MPII ionic liquid shows the highest efficiency of 9.35%. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.